PENGEMBANGAN MEDIA POCKED BOOK BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN LITERASI DIGITAL SISWA KELAS IV SDN MODANGAN 05 KECAMATAN NGLEGOK - UMI CHABIBAH; Mohamad Fatih, M.Pd; Cindya Alfi (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This study aims to 1) Maintain Pocket Book Design based on Augmented Reality (AR) Developed on Plant Body Part Materials and Its Functions in IPA Lectures (2 Knowledge of the Applicability of Pocket Books Learning Media based on augmented reality) As the Learning Media for Plant Body Body Parts and its Functions on IPA Lektures (3 Knowing the Improvement of Student Digital Literacy on Body Part Matters and Functions After Using the Augmenced Reality Based Book Pocket Media (AR). In this study using Research and Development Methods (Research and Development) Data sources in this study consist of primary data obtained from the research environment, namely SDN Modangan 05 Districts Nglegok, with research subjects totaling 24 students of class IV, consisting of 19 male students and 5 female students. Research results show that 1) The development of media pocket book based on augmented reality material parts of the plant body and its function is carried out through the stages of define, design, development, and disseminate. The phase involves observation, validation by media and material experts, as well as field trials with students of Class IV SDN Modangan 05. 2) The product validation results showed a score of 66, which after being processed in the presentation formula was 97%. The scores show that the augmented reality based media pocket book is valid and suitable for use in learning activities. Analysis of digital literacy improvement data using augmented reality-based pocket book media showed a comparison of 0.6830 between pre-angket and post-angkat. Based on the N-Gain level criteria, this study falls into the middle category